Non‐coding RNA regulatory networks in post‐transcriptional regulation of VEGFA in cancer. Issue 1 (10th May 2022) - Fontemaggi, Giulia
Abstract: The switch from the normal quiescent vasculature to angiogenesis in tumors is induced by a variety of growth factors, released from cancer and stromal cells upon oxygen and nutrients deprivation. Vascular endothelial growth factor A (VEGF‐A) is a potent‐secreted mitogen and the only growth factor specific to endothelial cells that is observed almost ubiquitously at sites of angiogenesis. Expression of VEGF‐A in cancer cells is controlled through transcriptional and post‐transcriptional mechanisms. Post‐transcriptional regulation of VEGF‐A occurs at multiple levels, through the control of splicing, mRNA stability and translation rate, enabling a fine‐tuned expression and release of VEGF‐A. Mounting evidence is highlighting the important role played by microRNAs (miRNAs) in the control of VEGF‐A mRNA stability and translation in cancer. Moreover, non‐coding RNAs, as long non‐coding RNAs and circular RNAs, are emerging as crucial modulators of VEGF‐A‐targeting miRNAs, with consequent ability to modulate VEGF‐A expression. This review discusses the recent progress on the ncRNA‐related networks controlling VEGF‐A expression in cancer cells and provides insights into the complexity of VEGF‐A post‐transcriptional regulation.